Levels of Questions used by English Teachers at SMP Negeri Poso Kota Utara - Vivin Krismawati Modjanggo (Sintuwu Maroso Journal of English Teaching, 2018)
The objectives of this research are to find out level of questions used by the teachers in teaching English at SMP Negeri Poso Kota Utara and to find out of students’ responses from the teacher’s questions. Researcher uses descriptive qualitative method. The data of this research is obtained from observation at SMP5 Poso Kota Utara and SMP 1 Poso Kota Utara. The result of this research showsthat knowledge, comprehension and evaluation are the most frequently used levelof questions, while the students’ responses are correct, incomplete, and no response.Keywords: levels of question, Bloom’s taxonomy, EFL teachers, EFL students